Hexagonal Boron Nitride: Glass Transition and Crystallization in Hexagonal Boron Nitride: Crucial Role of Orientational Order (Adv. Theory Simul. 2/2020). Issue 2 (17th February 2020) - Ravinder, R.; Garg, Prateet; Krishnan, N. M. Anoop
Abstract : The front cover shows two‐dimensional hexagonal boron nitride sheets that are obtained from melt‐quenching. As described by N. M. Anoop Krishnan and co‐workers in article number 1900174, the structures exhibit a polycrystalline or glassy structure depending on the cooling rate. Furthermore, these structures are stable at room temperature, although they exhibit significant out‐of‐plane deflections.